The importance of hypoxia and extra physiologic oxygen shock/stress for collection and processing of stem and progenitor cells to understand true physiology/pathology of these cells ex vivo. Issue 4 (July 2015) - Broxmeyer, Hal E.; O'Leary, Heather A.; Huang, Xinxin; Mantel, Charlie
Abstract : Purpose of review: Hematopoietic stem (HSCs) and progenitor (HPCs) cells reside in a hypoxic (lowered oxygen tension) environment, in vivo . We review literature on growth of HSCs and HPCs under hypoxic and normoxic (ambient air) conditions with a focus on our recent work demonstrating the detrimental effects of collecting and processing cells in ambient air through a phenomenon termed extra physiologic oxygen shock/stress (EPHOSS), and we describe means to counteract EPHOSS for enhanced collection of HSCs. Recent findings: Collection and processing of bone marrow and cord blood cells in ambient air cause rapid differentiation and loss of HSCs, with increases in HPCs. This apparently irreversible EPHOSS phenomenon results from increased mitochondrial reactive oxygen species, mediated by a p53-cyclophilin D– mitochondrial permeability transition pore axis, and involves hypoxia inducing factor-1α and micro-RNA 210 . EPHOSS can be mitigated by collecting and processing cells in lowered (3%) oxygen, or in ambient air in the presence of, cyclosporine A which effects the mitochondrial permeability transition pore, resulting in increased HSC collections. Summary: Our recent findings may be advantageous for HSC collection for hematopoietic cell transplantation, and likely for enhanced collection of other stem cell types. EPHOSS should be considered when ex-vivo cell analysis is utilized for personalized medicine, as metabolism of cells and their response to targeted drug treatment ex vivo may not mimic what occurs in vivo .